(untitled) (American Journal of Islam and Society, 2003)
The international seminar on Peace, Jihad & Conflict Resolution, jointly organized by AMSS, IIIT, and the Islamic Educational, Scientific and Cultural Organization (ISESCO), was hosted by the Center for Muslim- Christian Understanding (CMCU), Georgetown University on November 2- 3, 2002. The seminar’s goal was to bring a deeper understanding of the place and position of religion in general, and Islam in particular, toward the dynamic concepts of peace, jihad, political violence, and military conflict. The seminar got off to a lively start on Saturday morning with introductions presented by Dr. Jamal Barzinji (vice president, IIIT). Welcoming remarks were made by Dr. Ahmad S. Weld Abah (chairman, ISESCO Executive Council), Dr. Louay Safi (AMSS president), and Dr. John Esposito (CMCU director). The opening session was followed by an inspiring speech by Dr. Taha Jaber al-Alwani (president, Graduate School of Islamic and Social Sciences [GSISS]), on “Concepts between Islamic and Western Worldviews: Jihad as an Example.” Al-Alwani analyzed the meaning of peace, jihad, and conflict resolution from an Islamic jurisprudential perspective by examining how these concepts are governed by the values of tawhid (unity of God), tazkiah (purification of humanity), and ‘imran (establishing a values-based civilization). He discussed how practicing and establishing peace is obligatory for all people, because Islam considers humanity to be one family. Since most of Islam’s jurisprudential rules are based on peace, according to al-Alwani, “both peace and jihad have different levels, and each one should be fulfilled by individuals, family, and society.” He characterized jihad as: “There is no other concept that will match the meaning of peace in Islam except jihad,” and argued that “jihad is based on different levels: to struggle is the major meaning of jihad, in order to elevate oneself to a higher level, they must strive.” The concept of conflict resolution implies that many stages should be applied and negotiated before resorting to war. Thirty-two papers were presented in eight consecutive panels during the 2-day seminar. The panelists approached the issues from theoretical perspectives and sociopolitical experiences in order to overcome stereotypical discussions and superficial impressions. On the first day, the following subthemes were analyzed in four panels: “Jihad, War and Peace in the Islamic Authoritative Texts,” “Positive Attitude toward the ‘Other’,” “Religion: A Tool for Conflict Resolution,” and “Religious and Cultural Roots of War and Peace.” These panels drew attention to the need of developing an authentic methodology that deals objectively with religious texts and history. In the first panel, Dr. Jamal Badawi (St. Mary’s University, Canada) offered a new vision in his analysis of how some misunderstood verses and ahadith have left a negative impact upon the nature of Muslim and non-Muslim relations. He addressed such questions as: “Does Islam teach hate toward others?” ...